Adoption of recommended practices and basic technologies in a low-income setting. Issue 5 (30th January 2014) - English, Mike; Gathara, David; Mwinga, Stephen; Ayieko, Philip; Opondo, Charles; Aluvaala, Jalemba; Kihuba, Elesban; Mwaniki, Paul; Were, Fred; Irimu, Grace; Wasunna, Aggrey; Mogoa, Wycliffe; et al.
Abstract : Objective: In global health considerable attention is focused on the search for innovations; however, reports tracking their adoption in routine hospital settings from low-income countries are absent. Design and setting: We used data collected on a consistent panel of indicators during four separate cross-sectional, hospital surveys in Kenya to track changes over a period of 11 years (2002–2012). Main outcome measures: Basic resource availability, use of diagnostics and uptake of recommended practices. Results: There appeared little change in availability of a panel of 28 basic resources (median 71% in 2002 to 82% in 2012) although availability of specific feeds for severe malnutrition and vitamin K improved. Use of blood glucose and HIV testing increased but remained inappropriately low throughout. Commonly (malaria) and uncommonly (lumbar puncture) performed diagnostic tests frequently failed to inform practice while pulse oximetry, a simple and cheap technology, was rarely available even in 2012. However, increasing adherence to prescribing guidance occurred during a period from 2006 to 2012 in which efforts were made to disseminate guidelines. Conclusions: Findings suggest changes in clinical practices possibly linked to dissemination of guidelines at reasonable scale. However, full availability of basic resources was not attained and major gaps likely exist between the potential and actual impacts of simple diagnostics and technologies representing problems with availability, adoption and successful utilisation. These findings are relevant to debates on scaling up in low-income settings and to those developing novel therapeutic or diagnostic interventions.